The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3382/ps/pex071
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methionine supplementation in chicken feed on the quality and shelf life of fresh poultry meat

Abstract: The aim of this study was to investigate the influence of different methionine sources and concentrations on the quality and spoilage process of broiler meat. The trial was comprised of 7 treatment groups: one basal group (suboptimal in Methionine+Cysteine; i.e., 0.89, 0.74, 0.69% in DM SID Met+Cys in starter, grower, and finisher diets, respectively) and 3 doses (0.10, 0.25, and 0.40%) of either DL-Methionine (DLM) or DL-2-hydroxy-4-methylthio butanoic acid (DL-HMTBA) on an equimolar basis of the DLM-suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
2
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 56 publications
5
14
2
3
Order By: Relevance
“…e pH value was closely related to the cooking loss, thawing loss, and color values of the poultry filets, which is in accordance with former studies [21,35,36]. Even though the dietary composition and breed were reported to have an impact on water holding capacity of the meat [27,[37][38][39], no differences in cooking and thawing loss could be detected between the production lines in this study. e L * values showed no significant difference between groups but were higher than the optimal range for poultry reported in former studies [36,[40][41][42].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…e pH value was closely related to the cooking loss, thawing loss, and color values of the poultry filets, which is in accordance with former studies [21,35,36]. Even though the dietary composition and breed were reported to have an impact on water holding capacity of the meat [27,[37][38][39], no differences in cooking and thawing loss could be detected between the production lines in this study. e L * values showed no significant difference between groups but were higher than the optimal range for poultry reported in former studies [36,[40][41][42].…”
Section: Discussionsupporting
confidence: 90%
“…e abandonment of antibiotics showed no impact on microbial contamination or growth in this study. For both groups, the microbial shelf life was in accordance with the sensory shelf life and is in the normal range for fresh, aerobically packaged poultry [37]. Shorter shelf lives for similar products were reported as well but could be related to higher initial microbial contamination [16,52,53].…”
Section: Discussionsupporting
confidence: 70%
“…Indeed, a relationship between Met supplementation and bacterial counts on the meat surface has been reported, but the results are contradictory. While Aksu et al [21] detected lowering bacterial counts with increasing dietary Met concentrations, Albrecht et al [24] found a supporting effect on microbial growth. In fact, there is a lack of studies focusing on the relationship between the microbial growth and the shelf life of the meat and Met supplementation.…”
Section: Introductionmentioning
confidence: 97%
“…Lipid oxidation is a major factor during the spoilage of fresh meat and influences consumer acceptance of the product [30]. Furthermore, a positive effect on the sensory acceptance in comparison to the control group was reported by Albrecht et al [24]. However, it became evident during the laboratory trial that a large number of samples expressed white striping (WS), a breast myopathy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation